INTEGRASI PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS UNTUK ESTIMASI STOK KARBON HUTAN MANGROVE KAWASAN SEGOROANAK PADA KAWASAN TAMAN NASIONAL ALAS PURWO BANYUWANGI, JAWA TIMUR - , HENDRY FRANANDA, S. Pi, Prof. Dr. Hartono, DEA, DESS ([Yogyakarta] : Universitas Gadjah Mada, 2012)
estimate with Nowadays, forest carbon stocks estimate have been terrestrial methods, not utilize the remote sensing data. The ability of remote sensing data was more efficient in time, expense, and energy aspect compared with terrestrial methods, but terrestrial methods give higher accuracy rather than remote sensing. carbon stocks from each vegetation index transformations (SR, NDVI, This study tried to determining the ability of remote sensing data, and to ensure the most optimum vegetation index transformations in estimating mangrove forest carbon stocks. Correlation between each vegetation index transformations and the stocks carbon in study area include each accuracy level was resulted relate to the aim of this study. Counting the carbon stocks in every sample to be correlated with each vegetation index values was used as the method of this study. Accuracy assessment was done by compare with actual data to ensure the accuracy each vegetation index transformations. TVI, RVI, SAVI, EVI) c The result of this study was the correlation includes the level of accuracy and total ompared with actual data. EVI and TVI were the best transformations to estimating carbon stocks with R2 values of EVI = 0,72 and TVI = 0,63, with accuracy of EVI Â± 74.40139 tons/ha and TVI Â± 39.70762 tons/ha. The conclusion from this study, known vegetation index EVI and TVI is an index that has the best correlation and accuracy, EVI and TVI is the best vegetation index for estimating the mangrove forest carbon. Estimation of total carbon in Segoroanak mangrove forest area covering 1.368 ha for EVI transformation is 600.569 tons and 583.981 tons of TVI transformation.